Impact of MIF Gene Promoter Polymorphism on F508del Cystic Fibrosis Patients - Melotti, Paola; Mafficini, Andrea; Lebecque, Patrick; Ortombina, Myriam; Leal, Teresinha; Pintani, Emily; Pepermans, Xavier; Sorio, Claudio; Assael, Baroukh Maurice (PloS one, 2014)
Macrophage migration Inhibitory Factor (MIF) is a pro-inflammatory cytokine sustaining the acute response to gram-negative bacteria and a regulatory role for MIF in Cystic Fibrosis has been suggested by the presence of a functional, polymorphic, four-nucleotide repeat in this gene's promoter at position -794, with the 5-repeat allele displaying lower promoter activity. We aimed at assessing the association of this polymorphism with disease severity in a group of Cystic Fibrosis patients homozygous for F508del CFTR gene mutation. Genotype frequencies were determined in 189 Cystic Fibrosis and 134 control subjects; key clinical features of patients were recorded and compared among homozygous 5-allele patients and the other MIF genotypes. Patients homozygous for the 5-repeat allele of MIF promoter displayed a slower rate of lung function decline (p = 0.027) at multivariate survival analysis. Multiple regression analysis on age-normalized respiratory volume showed no association of the homozygous 5-repeat genotype with lung function under stable conditions and no correlation with P.aeruginosa chronic colonization. Therefore, only the Homozygous 5-repeat genotype at MIF -794 is associated with milder disease in F508del Cystic Fibrosis patients.